ِِAl-imam Al-baidowi wa Arauhu Haula Annasakh"Dirasah Tahliliyah Kitab Anwaruttanzil wa Asrarutta'wil" - Baidowi, Mahmut; , DR. M. Muinudinillah; , Dr. Imron Rosyadi M.Ag (2016)
Understanding the naskh wal mansukh (abrogating and abrogated) plays a great role in understanding the Holy Qur'an. This knowledge will be beneficial for scholars of fiqh, usul and tafsir. Because of its importance, the al-salaf al-ṣāliḥ considered that understanding nasakh and manshukh is a requirement for the mufassir in interpreting the Qur'an, and for the muhaddiths in a hadith narrated and for the fuquha ' in conducting ijtihad and issuing a fatwa. Jalaluddin Suyuti writes in al-Itqan that a person once claimed before Ali bin Abu Talib that he had acquired good command on the knowledge of the Koran. Ali asked him, "Can you distinguish naskh from mansukh?" The man replying that he did not know the difference, Ali advised the man that he had endangered not only his own soul, but the souls of his listeners. Hence, it is clear that nask wal masukh lights the way for the mufassir in interpreting the Qur'an and for the fuquha ' in conducting ijtihad before issuing a fatwa Naskh wal mansukh is a very important discussion that has always been a debate among scholars of the antiquity to the present. It also create contentious relationship between the Muslims and the non Muslims like Jews and Christians about what is allowed and what is not. Indeed, the enemies of Islam like the Orientalists and missionaries have made Naskh wal mansukh as a weapon to weaken Islam. They trick some of muslim scholars into believeing that there is no Naskh wal Mansukh; hence it creates assumption that there are contradictions in the Qur'an. In accordance to that fact, some scholars give very serious attention regarding Naskh wal Mansukh, and have written a book specifically on that subject, or make a certain chapter on that subject in his works. Among these scholars are Qatada bin Da'amah Assudusi, Abu Abdul Qasim ibn Sallam and Imam Nashirudin al- Baidowi. This thesis discusses the opinions of some prominent sholars regarding the Naskh wal Mansukh in the Quran. Most parts of this work highlights the work of Imam Nashirudin Al-Baidowi titled "Anwar al-Tanzil wa Asrar al-Ta'wil". Nashirudin Al-Baidowi is well known as the scholar of ushul fiqh and mufassir.